Prompt and delayed secondary excitons in rare gas solids: Spectroscopy in Cryocrystals and Matrices - Kirm, M.; Kisand, V.; Sombrowski, E.; Steeg, B.; Vielhauer, S.; Zimmerer, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Direct and indirect creation of excitons in rare gas solids has been investigated with reflectivity and luminescence spectroscopy. For the heavy rare gas solids Kr and Xe, new and more reliableexciton parameters have been deduced. With time-resolved luminescence spectroscopy, fast and delayed secondary-exciton creation has been established and separated. Thermalization of photocarriers and their delayed recombination have been analyzed, including a first attempt to investigate the influence of excitation density on the carrier dynamics. The existence of excitonic side bands of ionization limits Ei (either band gap or inner-shell ionization limits) in prompt secondary exciton creation has been established. The threshold energies of these side bands are given by Eth≈Ei nEex (n is integer, Eex is exciton energy). The side bands are ascribed to the formation of electronic polaron complexes, superimposed to inelastic scattering of photoelectrons.